Novel Monoclonal Antibodies Recognizing Human Prostate-Specific Membrane Antigen (PSMA) as Research and Theranostic Tools - Nováková, Zora; Foss, Catherine A; Copeland, Benjamin T; Morath, Volker; Baranová, Petra; Havlínová, Barbora; Skerra, Arne; Pomper, Martin G; Barinka, Cyril (The Prostate, 2017)
BACKGROUND: Prostate-specific membrane antigen (PSMA) is a validated target for the imaging and therapy of prostate cancer. Here, we report the detailed characterization of four novel murine monoclonal antibodies (mAbs) recognizing human PSMA as well as PSMA orthologs from different species. METHODS: Performance of purified mAbs was assayed using a comprehensive panel of in vitro experimental setups including Western blotting, immunofluorescence, immunohistochemistry, ELISA, flow cytometry, and surface-plasmon resonance. Furthermore, a mouse xenograft model of prostate cancer was used to compare the suitability of the mAbs for in vivo applications. RESULTS: All mAbs demonstrate high specificity for PSMA as documented by the lack of cross-reactivity to unrelated human proteins. The 3F11 and 1A11 mAbs bind linear epitopes spanning residues 226-243 and 271-288 of human PSMA, respectively. 3F11 is also suitable for the detection of PSMA orthologs from mouse, pig, dog, and rat in experimental setups where the denatured form of PSMA is used. 5D3 and 5B1 mAbs recognize distinct surface-exposed conformational epitopes and are useful for targeting PSMA in its native conformation. Most importantly, using a mouse xenograft model of prostate cancer we show that both the intact 5D3 and its Fab fragment are suitable for in vivo imaging. CONCLUSIONS: With apparent affinities of 0.14 and 1.2 nM as determined by ELISA and flow cytometry, respectively, 5D3 has approximately 10-fold higher affinity for PSMA than the clinically validated mAb J591 and, therefore, is a prime candidate for the development of next-generation theranostics to target PSMA. Prostate 77:749-764, 2017. © 2017 Wiley Periodicals, Inc.
Keywords: myší monoklonální protilátky; NAALADase; Male; monoklonální protilátky; antigeny povrchové; glutamátkarboxypeptidasa II; Prostate; Xenograft Model Antitumor Assays; Prostatic Neoplasms; Glutamate Carboxypeptidase II; mužské pohlaví; prostata; monoclonal antibody; Theranostic Nanomedicine; prostate cancer; glutamate carboxypeptidase II; xenogenní modely - testy protinádorové aktivity; Animals; lidé; Humans; zvířata; Antibodies, Monoclonal, Murine-Derived; nádory prostaty; Antigens, Surface; myši; teranostická nanomedicína; Antibodies, Monoclonal; Mice; in vivo imaging